Characterisation Two Types of Feed on Production Performances of Laying Hen in Blitar Regency, East Java - Rafwan Afandi; Budi Hartono; Irfan H. Djunaidi (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
This study was conducted to compare the use of two types of feed on production performances of laying hen (feed consumption, egg production, feed conversion ratio, and population depletion) in Blitar Regency. Data were collected from several laying hen farms in Blitar Regency with survey method. All data were then analyzed both qualitatively and quantitatively. The average feed price of semi self-mixed feed and total self-mixed feeds were Rp 5,031 and Rp 4,752 per kg. Hen received semi self-mixed feed in one period showed 117.5 g/hen/day of feed intake, 70.38% of egg production, 2.62 of feed conversion ratio, and 20.50% of population depletion. Meanwhile, the total self-mixed feed resulted 118.23 g/hen/day of feed consumption, 71.75% of egg production, 2.39 of feed conversion ratio, and 15.94 of population depletion in one period. The proximate analysis showed that the total self-mixed feed had better nutrient balance compared to semi self-mixed feed, based on SNI 01-3929-2006 standard. As conclusion the total self-mixed feed showed more optimal production performances than semi self-mixed feed.